General Ne Win a political biography - Taylor, Robert H. 1943- (Institute of Southeast Asian Studies, 2015)
Offers an illuminating study of Ne Win, the most controversial of the first generation of post-independence Southeast Asian leaders, and how he steered Burma (now Myanmar), through the Cold War years. This book is a significant contribution to the historiography of Myanmar and its unnoticed role in the Cold War in Asia.